Fucoidan attenuates radioiodine-induced salivary gland dysfunction in mice - Kim, Young-Mo (BMC Oral Health, 2019)
BACKGROUND: Radioiodine (RI) treatments can destroy the cellular components of salivary glands (SG) and disrupt their function. This study investigated whether fucoidan could attenuate radioiodine-induced SG dysfunction in a mouse model. METHODS: Female C57BL/6 mice (n = 36) were classified into three groups; i) a normal (control) group, ii) an RI-treated group (0.2 mCi/20 g mouse, administered orally), and iii) a fucoidan and RI-treated group. Mice in each group were classified into three subgroups and sacrificed at 2, 4, and 12 weeks after RI treatment. The measurements of salivary flow rates and lag times and histomorphologic examinations were performed, and apoptotic assays were conducted. Changes in salivary (99m)Technetium (Tc)-pertechnetate parameters using single-photon emission computed tomography were followed. RESULTS: Salivary flow rates and lag times in the fucoidan group were improved compared to the RI-treated group. Histologic examinations of SGs in the fucoidan group showed mucin-rich parenchymal areas and reduced periductal fibrosis as compared to the RI-treated group. Moreover, compared with the RI-treated group, fucoidan-treated groups showed evidence of cytoprotection, with a greater number of salivary epithelial cells and myoepithelial cells being observed. Fewer apoptotic cells were observed in the fucoidan group as compared to the RI group. The extent of (99m)Tc pertechnetate excretion in the fucoidan group was similar to that of the control group. CONCLUSION: Our results demonstrate that fucoidan administration before RI treatment could attenuate RI-induced SG damage and provides a possible candidate for preventing SG damage induced by RI.